2010
DOI: 10.1097/wno.0b013e3181dee8c6
|View full text |Cite
|
Sign up to set email alerts
|

Cup-to-Disc Ratio in Patients With Idiopathic Intracranial Hypertension Is Smaller Than That in Normal Subjects

Abstract: The C:D ratio in our IIH population was smaller than that in published control populations. A small C:D ratio may lower the threshold for developing optic disc edema from ischemia, increased intracranial pressure, or other mechanisms. Additional studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Glaucomatous optic neuropathy is characterized by thinning of the neural rim and enlargement of CV. The opposite characters are seen in IIH . However, an overcrowded disc cup can be physiological .…”
Section: Discussionmentioning
confidence: 92%
“…Glaucomatous optic neuropathy is characterized by thinning of the neural rim and enlargement of CV. The opposite characters are seen in IIH . However, an overcrowded disc cup can be physiological .…”
Section: Discussionmentioning
confidence: 92%
“…10 Likewise, translaminar pressure with subsequent optic nerve damage in primary open angle glaucoma (POAG) can manifest as a typical glaucomatous cupping with an increased CDR. 11 Although two previous studies of IIH have documented a smaller CDR in patients with IIH with papilloedema (IIHWP) as compared with normal subjects, 13,14 to our knowledge, no prior study has examined the CDR in patients with IIHWOP. Based upon our initial clinical impressions about CDR in IIH, we hypothesised that, as in NAION, a small CDR might be a structural risk factor for the development of IIHWP and a larger CDR might be associated with IIHWOP.…”
Section: Introductionmentioning
confidence: 95%
“…26,27 Investigations into the association between optic cup size and ODE development due to causes other than NAION are limited. To date, 2 studies have reported that patients with IIH have smaller cup-disc ratios than do normal controls after the ODE resolves, 16,17 and a third study identified that patients with IIH and papilledema have smaller cup-disc ratios after ODE resolution than do patients with IIH who never developed papilledema. 15 Although the present study also found that optic cup size (quantified as cup volume, width, or depth) is associated with ODE development, an association between cupdisc ratio and ODE was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…This discat-risk profile has been associated with at least 2 terrestrial conditions involving ODE both in the absence and presence of elevated intracranial pressure. Specifically, a crowded ONH is a risk factor for nonarteritic anterior ischemic optic neuropathy (NAION) [9][10][11][12][13][14] and may be associated with an increased risk of papilledema in idiopathic intracranial hypertension (IIH), [15][16][17] a condition that shares several clinical findings with SANS, including ODE, chorioretinal folds, and globe flattening. A second potential factor is higher body weight, which has been reported to have an association with the presence of ODE and choroidal folds after spaceflight.…”
mentioning
confidence: 99%